148k views
0 votes
For f(x) = 3x +1 and g(x) = x2 – 6, find (f- g)(x).

User Mrzo
by
6.3k points

1 Answer

4 votes

Answer:


\boxed{\sf (f-g)(x) = -{x}^(2) + 3x + 7}

Given:


\sf f(x) = 3x + 1 \\ \sf g(x) = {x}^(2) - 6

To find:


\sf (f - g)(x) = f(x) - g(x)

Explanation:


\sf \implies(f - g)x = f(x) - g(x) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (3x + 1) - ( {x}^(2) - 6) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (3x + 1) + (- {x}^(2) + 6) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 3x + 1 - {x}^(2) + 6 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = - {x}^(2) + 3x + 1 + 6 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = -{x}^(2) + 3x + 7

User Cyperpunk
by
6.3k points